Os anos 30 no século XXI - Félix, Márcio Luiz Mourilhe (2004)
The main objective of the present study is to identify witch administration tools can be used by the managers to accelerate the change process, increasing the productivity of process and people of Information Technology area. It also studied the administration tools of first three decades of XX century, when the Fordist paradigm was strongly present, and the last three decades of the same century, called Flexibilization period, still be applied to manage an IT area of large company witch their processes are totally based on software and computers. The study has an empirical section based on a case study of Information Technology area of Infoglobo Comunicações, where mean processes were changed to comply with new quality and productivity standards defined by the company's board.